2019
DOI: 10.4300/jgme-d-18-00896.1
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Stories to Build Resilience: Articulating the Common Threads That Connect Us

Abstract: The protocol-driven aspect of the mnemonic refers to ALEEN, a method developed by Peter Pronovost, MD, to respectfully communicate with upset patients. It stands for Anticipate their anger and do not take it personally, Listen without interrupting, Empathize with what they are saying, Explain what happened and why, and Negotiate a way forward. We use this same protocol to communicate respectfully with distressed residents. If a resident is upset about a program director's decision, being heard and receiving an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Narrative medicine practice also serves to foster a sense of community. In a story-telling venue, medical faculty and staff were invited to share stories from the hospital, and in doing so learned that they were “not alone” in their experiences [ 30 ]. In contrast to much of classical medical training, hierarchy is limited in the study of narrative.…”
Section: Utilizing Narrative To Develop Doctoring Skillsmentioning
confidence: 99%
“…Narrative medicine practice also serves to foster a sense of community. In a story-telling venue, medical faculty and staff were invited to share stories from the hospital, and in doing so learned that they were “not alone” in their experiences [ 30 ]. In contrast to much of classical medical training, hierarchy is limited in the study of narrative.…”
Section: Utilizing Narrative To Develop Doctoring Skillsmentioning
confidence: 99%
“…Several initiatives have been designed to address detachment and combat burnout by promoting social connection. Examples include reflection groups, structured social events, individual wellness check-ins by chief residents, resilience workshops, and sharing stories about patient care [6,7,8,9,10,11,12,13,14,15]. Many of these initiatives, while anecdotally beneficial, require considerable institutional resources and trainee time.…”
Section: Finding Meaning and Communitymentioning
confidence: 99%
“…A variety of anti-burnout strategies have been tried to enhance connection, with many in the form of story sharing about clinical care [1,6,7,9,15]. While anecdotally beneficial, these efforts may require sizeable time and resources to set up and lack specificity in regards to institutional and cultural aspects of detachment.…”
Section: A Low-effort Low-cost Approach To Foster Communication Connection and An Overall Healthy Educational Communitymentioning
confidence: 99%
“…The event featured residents, fellows, and faculty sharing 750-word stories they had prepared in advance. We demonstrated that the approach was both feasible and well-accepted [ 22 ].…”
Section: Introductionmentioning
confidence: 99%